Calcium Dobesilate for Prevention of Gentamicin-induced Nephrotoxicity in Rats (Iranian Journal of Kidney Diseases, 2014)
Introduction. Calcium dobesilate is an antioxidant drug and this study is aimed to investigate the effects of calcium dobesilate on gentamicin-induced nephrotoxicity. Material and Methods. This experimental study was conducted on 40 male Sprague-Dawley rats. The rats were randomly divided into the following 5 groups: control, sham, gentamicin (100 mg/kg/d, intraperitoneal), gentamicin and calcium dobesilate (50 mg/kg body weight), gentamicin and calcium dobesilate (50 mg/kg body weight). Treatment was provided once a day in a 7-day period. At the end of the 7th day, plasma and urine samples were taken and the concentrations of creatinine, urea nitrogen, sodium, potassium, and osmolarity were measured in both samples. The level of oxidative stress in the left kidney tissue samples was also assessed by measuring malondialdehyde and ferric reducing antioxidant power. Results. Calcium dobesilate intake with both doses led to a significant decrease in the elevated concentration of creatinine, urea nitrogen, and fractional excretion of sodium by gentamicin, and an increase in creatinine clearance and absolute excretion of potassium as compared to the gentamicin group. Furthermore, calcium dobesilate decreased tissue malondialdehyde and increased tissue ferric reducing antioxidant power at both doses, in comparison to those in the gentamicin group. Conclusions. Calcium dobesilate is capable of protecting rats against gentamicin-induced nephrotoxicity. This protective effect of calcium dobesilate is probably dependent on its antioxidant properties.